2006
DOI: 10.1007/s11095-006-9031-4
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Modeling of Nitric-Oxide-Associated Reaction Network

Abstract: The model predicts that concurrent high nitric oxide and superoxide generation--such as in the inflammatory conditions--may result in nonlinear system dynamics, and glutathione may serve as a dynamic switch of N203 mediated nitrosation reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 48 publications
1
23
0
Order By: Relevance
“…The reaction of peroxynitrite with glutathione (GSH) (present at mM levels) was neglected because of a two order magnitude slower reaction rate constant (k=6.6×10 2 M −1 .s −1 ) difference as compared to reaction rate constant with CO 2 (k=1–2×10 4 M −1 .s −1 ) [17, 81]. However, NO (indirectly through its oxidation product N 2 O 3 ) and peroxynitrite (directly or through products of peroxynitrite decomposition and its reaction with CO 2 ) can nitrosate glutathione to form S- nitrosoglutathione (GSNO) [8183], which is involved in a number of physiological processes including apoptosis, and response to oxidative and nitrosative stress [84, 85]. Overall, our results are in agreement with other studies that reported the lack of a plateau in peroxynitrite concentration [17].…”
Section: Discussionmentioning
confidence: 99%
“…The reaction of peroxynitrite with glutathione (GSH) (present at mM levels) was neglected because of a two order magnitude slower reaction rate constant (k=6.6×10 2 M −1 .s −1 ) difference as compared to reaction rate constant with CO 2 (k=1–2×10 4 M −1 .s −1 ) [17, 81]. However, NO (indirectly through its oxidation product N 2 O 3 ) and peroxynitrite (directly or through products of peroxynitrite decomposition and its reaction with CO 2 ) can nitrosate glutathione to form S- nitrosoglutathione (GSNO) [8183], which is involved in a number of physiological processes including apoptosis, and response to oxidative and nitrosative stress [84, 85]. Overall, our results are in agreement with other studies that reported the lack of a plateau in peroxynitrite concentration [17].…”
Section: Discussionmentioning
confidence: 99%
“…Following this, the remaining differential equations are added one by one, and bistability is checked each time a new reaction is added to finally obtain the whole set of equations in the apoptotic pathway. The rate constants of these reactions are taken from the literature (Bagci et al 2008) and (Hu et al 2006). This procedure is used for both models 1 and 2.…”
Section: Methodsmentioning
confidence: 99%
“…In their mathematical model, NO-related reactions were integrated into the mitochondriadependent apoptosis model (Bagci et al 2006). The kinetic parameters of the simulations were selected from a wide parameter range in the literature (Hu et al 2006). Computations on this model aimed to understand the regulatory effect of the reactive NO species namely N 2 O 3 , non-heme iron nitrosyl species (FeL n NO), and peroxynitrite (ONOO − ).…”
Section: Introductionmentioning
confidence: 99%
“…The kinetic models of NO, O 2 - , and ONOO − studied diverse aspects of roles of these molecules, which included (1) the kinetics of reaction of NO and superoxide, 46-48 (2) superoxide dismutation catalyzed by superoxide dismutase, 44,45,49,50 (3) role of GSH, 46 and (4) models of O 2 - production from mitochondrial transport chain.…”
Section: Kinetic Modelsmentioning
confidence: 99%